2022
DOI: 10.4329/wjr.v14.i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Chest radiological finding of COVID-19 in patients with and without diabetes mellitus: Differences in imaging finding

Abstract: The pandemic of novel coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Diabetes mellitus is a risk factor for developing severe illness and a leading cause of death in patients with COVID-19. Diabetes can precipitate hyperglycaemic emergencies and cause prolonged hospital admissions. Insulin resistance is thought to cause endothelial dysfunction, alveolar capillary micro-angiopathy and interstitial lung fibrosis through pro-inflammatory pathways. Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Insulin resistance and impaired glucose homeostasis have been shown to cause alveolar capillary microangiopathy and interstitial fibrosis due to super inflammation [ 72 ]. In addition, elevated HbA1c levels have been associated with inflammation and hypercoagulability, leading to an increased mortality rate in patients with diabetes with COVID-19 [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance and impaired glucose homeostasis have been shown to cause alveolar capillary microangiopathy and interstitial fibrosis due to super inflammation [ 72 ]. In addition, elevated HbA1c levels have been associated with inflammation and hypercoagulability, leading to an increased mortality rate in patients with diabetes with COVID-19 [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In situ microvascular thrombosis or immunothrombosis occurs due to alveolar injury, inflammatory storm, and disruption in the thromboprotective pulmonary vascular endothelium. The clinical results of COVID-19 are worse in patients with diseases associated with endothelial dysfunction, such as systemic hypertension, diabetes, and obesity [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, patients with the involvement of 50% of their parenchyma had higher fibrous scores than those with single lobe involvement. This may indicate that, in addition to detecting more airspace consolidation in diabetics, [32] vascular microemboli are highly involved in the pathogenesis. [33] One criticism of this work on COVID-19-related pulmonary fibrosis is the sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that, compared with normal infected individuals, patients with diabetes exhibit more severe conditions in terms of clinical course and chest imaging and are more likely to develop critical COVID-19 [ 5 , 7 , 8 ]. In addition, those with poor blood glucose control have a worse prognosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%